Two-sided markets and electronic intermediaries - Bruno Jullien (Center for Economic Studies and ifo Institute (CESifo), 2004)
The object of this paper is to discuss on-line intermediation from the perspective of two-sided markets. It builds a simple model of the intermediation activity when trading partners are involved in a commercial relationship and uses it to illustrate some of the results that emerge in the two-sided market literature, as well as to discuss some new aspects. The first part concentrates on a monopoly intermediation service and discusses both efficient pricing and monopoly pricing. The second part discusses the nature of competition between intermediaries, addressing issues as competitive crosssubsidies, multi-homing or tying.
Keywords: L40; L14; L13; L12; D85; D4; 330; intermediation; two-sided market; network; cross-subsidy; tying; Handel; E-Business; Service Provider; Theorie der Unternehmung; Betriebliche Preispolitik; Theorie